Synthesis And Characterization Of Azo Cross-Linked Polymer As A New Catalyst For The Production Of Hydrogen Gas By Methanolysis Of Nabh4 - Gokkus, Kutalmis; Gur, Mahmut; Butun, Vural (Aperta, 2024)
The intensive use of fossil fuels has profound impacts on all ecosystems, primarily contributing to global warming through greenhouse gas emissions. To mitigate these impacts, alternative energy sources like hydrogen are crucial. In this study, azo cross-linked polymer with 4-aminophenyl sulfone and resorcinol were synthesized by a green synthesis method. The polymer was extensively characterized by Fourier-transform infrared spectroscopy, Brunner-Emmett-Teller analysis, thermogravimetric analysis, and scanning electron microscopy-energy dispersive x-ray spectroscopy analyses. Subsequently, the catalytic performance of the polymer in hydrogen production from NaBH4 via methanolysis was investigated. At this stage, the parameters affecting hydrogen production (catalyst and NaBH4 amounts, MeOH volume and temperature) were systematically studied to determine optimum conditions. The maximum HGR values of the polymer was 13,100 and 27,000 mL min(-1) g(cat)(-1) at 30 and 60 degrees C, respectively and its activation energy was 10.45 kJ mol(-1). After optimization, the reusability of azo polymer was tested with 5 cycles. The theoretical volume of hydrogen was produced in all 5 cycles. But with each cycle, the hydrogen production time increased. The main purpose of this study was to demonstrate novel azo-linked polymers with high catalytic activity in hydrogen production. The results revealed significant potential of the polymer for hydrogen generation. Overall, this research highlights the promising role of azo cross-linked polymers as effective catalysts for hydrogen production, offering new perspectives and pathways towards sustainable energy solutions.